Studies on Antibiotic Sensitivity Pattern of Bacterial Isolates from Subclinical Mastitis of Sirohi Goats - Sharma, Shiv Kumar; Meena, Hitesh Kumar; Joshi, Monika (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Milk samples of 100 udder halves from 50 apparently healthy Sirohi goats were collected aseptically and subjected to bacteriological  culture examination to determine the prevalence of subclinical mastitis, type of bacterial isolates and their antibiotic sensitivity pattern.  The prevalence of subclinical mastitis was found to be 34 % by cultural examination of milk samples. In subclinical mastitic milk samples,  Staphylococci was found most prevalent organism (37.50 %) followed by Streptococci (28.12 %), E. coli (18.75 %), Bacilli (9.37 %) and  Corynebacterium Spp. (6.25 %). The antibiotic sensitivity pattern showed that the isolated bacteria were highly sensitive to amoxycillin
Keywords: Antibiotic sensitivity pattern; Culture examination; Sirohi goats; Subclinical mastitis